Sistem Monitoring Deteksi Kebakaran Bangunan Berbasis IOT dan Android dengan Google Maps API: System Monitoring of Fire Building Detection which Based on IOT and Android using Google Maps API - Zhafran Saloom; I Gde Putu Wirarama Wedashwara W; Ahmad Zafrullah M (Journal of Computer Science and Informatics Engineering (J-Cosine), 2023)
Fire is a natural disaster which is threateing and interfering life that was caused by nature, non-nature, so that the disaster will causing, casunlties, property loss also affecting psychologis. Designing structur whice expected could, defecting a fire base on the level of smoke concentration and flame which is happend in a building also sending a notice to the fire sighting unid. Designing system monitoring stucture using android with the use of Google map API as a location determination tool of the information of where the fire accured, so that owner of the building and the fire fight could geting a realtime effecture informetion using app base an android with internet of things and Google maps, utilized the use of internet of things also can be view of sends an information between cencor so in order that owner of the building can also monitoring online by the used of Google maps. Google maps is functioning to send position of the fool which was installed in the building the resuld foud that flame cencor could detecting the source of fire using wave length of light between 0 – 1032 nm and smoke cencor could detecting smoke concentration between 100 – 5000 ppm the with the use of MQTT protocol it will directly send to android. android can monitoring the fire information after that is determine the location of the fire by Google maps